2017
DOI: 10.1021/acsomega.7b00326
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Extracellular Polysaccharide Production and Self-Sustainable Electricity Generation for PAMFCs byScenedesmussp. SB1

Abstract: In this study, a freshwater microalga, Scenedesmus sp. SB1, was isolated, purified, and identified by its internal transcribed spacer region (ITS1-5.8S-ITS2). Media optimization through the Plackett–Burman Design and response surface methodology (RSM) showed a maximum exopolysaccharide (EPS) production of 48 mg/L (1.8-fold higher than that for unoptimized media). Characterization using gas chromatography–mass spectrometry, Fourier transform infrared, X-ray diffraction, and thermogravimetric analysis reveals th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 51 publications
1
20
0
Order By: Relevance
“…One mechanism of possible retention is the production of extracellular polymeric substances (EPS). Algae and bacteria produce EPS which can alter the physical and chemical environment around their cells (Angelaalincy et al, 2017;Stibal et al, 2012a). For example, it has been shown that EPS are used by cyanobacteria in cryoconite holes to bind mineral particles together creating the cryoconite granules at the bottom of the hole (Yallop et al, 2012;Musilova et al, 2016;Stibal et al, 2012b).…”
Section: Retention Of Nutrients At Ice Sheet Surfacementioning
confidence: 99%
“…One mechanism of possible retention is the production of extracellular polymeric substances (EPS). Algae and bacteria produce EPS which can alter the physical and chemical environment around their cells (Angelaalincy et al, 2017;Stibal et al, 2012a). For example, it has been shown that EPS are used by cyanobacteria in cryoconite holes to bind mineral particles together creating the cryoconite granules at the bottom of the hole (Yallop et al, 2012;Musilova et al, 2016;Stibal et al, 2012b).…”
Section: Retention Of Nutrients At Ice Sheet Surfacementioning
confidence: 99%
“…It is reported that increases in bacterial growth generate more exopolysaccharides. 15 RCB contributes increasing lipids and carbohydrates for GS1 to GS3 Figure 5. Frequency displacement observed in AMIDE regions for GS1 to GS3 respect from LB control, indicates a change of protein sources in the media composition, and could be responsible for the higher growing rates obtained in the design media Figure 5.…”
Section: Resultsmentioning
confidence: 99%
“…The types of MFCs that operate with a trielectrode system are commonly employed in electrochemical studies (Angelaalincy et al, 2017). The setup consists of three electrodes: the working electrode which acts as a cathode, mostly made up of glassy carbon or platinum electrode that accommodates the microbial consortium; the counter electrode, that functions as the electricity conductor and the reference electrode which is the standard electrode made up of silver in potassium chloride or silver.…”
Section: Elements Constituting Microbial Fuel Cellsmentioning
confidence: 99%
“…In such cases, it is inferred that, not the density of the biofilms, but the active electron transferring live organisms present in the outer layer of the biofilms, contribute to the high current generation of the system (Sun et al, 2016). In composition, apart from EPS, the biofim is also comprised of a major portion of polysaccharides and minor portions of glycoproteins, proteins, glycolipids, and negligible amount of nucleotides and in rare cases, some metals (Angelaalincy et al, 2017) that contribute to the structural and functional outlook of the biofilm. However, EPS comprises the major component of the biofilm matrix.…”
Section: Eps In Biofilm Formation and Regulationmentioning
confidence: 99%
See 1 more Smart Citation